2002
DOI: 10.1007/s005950200179
|View full text |Cite
|
Sign up to set email alerts
|

Giant Brunneroma as an Unusual Cause of Upper Gastrointestinal Hemorrhage: Report of a Case

Abstract: Brunneroma, also known as Brunner's gland adenoma or harmartoma, is a rare, benign, proliferative lesion arising from the Brunner's glands of the duodenum, usually discovered incidentally at endoscopy. Occasionally, these lesions manifest as a rare cause of duodenal obstruction or upper gastrointestinal hemorrhage, and require excision. We report a case of an unusually large Brunneroma in a patient who presented with fresh melena and anemia. Although endoscopic polypectomy is the treatment of choice, we decide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 6 publications
1
18
0
1
Order By: Relevance
“…This mostly concerns the hamartomas that are large in size and symptomatic. Symptomatic cases most often present with gastrointestinal bleeding or obstructive symptoms [1, 2, 6, 7, 9, 1214]. In rare cases, Brunner's gland hamartomas have been reported to cause duodenal intussusception [15, 16], “idiopathic” pancreatitis by intermittent obstruction of the Ampulla of Vater [17, 18], and mimicking of pancreatic or duodenal malignancy [15, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…This mostly concerns the hamartomas that are large in size and symptomatic. Symptomatic cases most often present with gastrointestinal bleeding or obstructive symptoms [1, 2, 6, 7, 9, 1214]. In rare cases, Brunner's gland hamartomas have been reported to cause duodenal intussusception [15, 16], “idiopathic” pancreatitis by intermittent obstruction of the Ampulla of Vater [17, 18], and mimicking of pancreatic or duodenal malignancy [15, 19, 20].…”
Section: Discussionmentioning
confidence: 99%
“…Brunner's gland adenoma that causes clinical symptoms is composed of hyperplastic Brunner's glands and contains mostly an admixture of glandular, adipose, and muscular tissues, as was the case in the studied case. 2 In barium examination, the findings are often nonspecific because there is usually a sessile or pedunculated polypoid-filling defect in the duodenal bulb. CT-Scan is promising as reported by Gourtsoyaiannis et al 3 It is still controversial whether asymptomatic Brunner's gland tumors found incidentally needs surgical removal.…”
Section: Discussionmentioning
confidence: 99%
“…5 There have been several reports that Brunner's gland tumors could give rise to acute profuse bleeding, resulting in hypovolemic shock in patients. 2,4,6,7 Conclusion Symptomatic Brunner's gland tumors, in the most accepted point of view, usually need surgical treatment. When the tumor is small or pedunculated, endoscopic polypectomy is the first choice.…”
Section: Discussionmentioning
confidence: 99%
“…1 Brunner's gland hyperplasia also known as Brunneroma or polypoid hamartoma is a rare, benign, proliferative lesion arising from the Brunner's glands of the duodenum. It accounts for 10.6% of benign tumors of the duodenum and rarely presents with any symptoms.…”
Section: Introductionmentioning
confidence: 99%